Effects of tetracycline on shedding of susceptible and resistant salmonella spp. experimentally inoculated into pigs - Claussen, K.M.; Hyatt, D.R.; Galland, J.C.; Nietfeld, Jerome C.; Sargeant, J.M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The objective of this experiment was to study the influence of tetracycline on the transfer of antibiotic resistance in an in vivo swine model experimentally infected with antibiotic-resistant and antibiotic susceptible Salmonella spp. Tetracycline reduced the amount and duration of shedding of tetracycline- susceptible Salmonella. However, tetracycline had no effect on shedding of resistant Salmonella. We also have evidence that resistance was transferred from the resistant to the susceptible strain of Salmonella.
Keywords: Swine; Salmonella typhimurium; Antibiotics; Resistance